1996
DOI: 10.3758/bf03197272
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of associates and activation of synonyms in the rare-word paradigm: Further evidence for a center-surround mechanism

Abstract: Two experiments investigated semantic priming effects in a modified version of the Dagenbach, Carr, and Barnhardt (1990) rare-word paradigm. After learning a list of rare words to a criterion of 50%recall, subjects participated in a lexical decision task in which the rare words served as primes. Whenthe targets were associatively related to the primes, lexical decision responses were facilitated following recalled definitions and inhibited following unrecalled definitions. When the targets were synonyms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Parallel findings have been observed in episodic memory experiments using homographs, which establish that inhibitory effects are recall specific, consistent with properties of retrieval-induced forgetting more generally (Shivde & Anderson, 2001). Finally, research using the rare-word paradigm has found that difficult semantic retrievals recruit inhibitory processes: When subjects struggle to recall the meaning of an unusual, infrequently encountered word that is weakly represented in memory, related concepts appear to be impaired (Barnhardt, Glisky, Polster, & Elam, 1996;Dagenbach, Carr, & Barnhardt, 1990; see also Thompson-Schill, 1997 for an interesting discussion of the role of the left prefrontal cortex in controlling selective retrieval from semantic memory). Taken together, these results argue that retrieval induced forgetting is not limited to episodic retrieval, or to taxonomic categories; rather, it is a general consequence arising whenever inhibitory mechanisms are recruited to guide selection in the face of competition from distracting memories.…”
Section: Generalitymentioning
confidence: 68%
“…Parallel findings have been observed in episodic memory experiments using homographs, which establish that inhibitory effects are recall specific, consistent with properties of retrieval-induced forgetting more generally (Shivde & Anderson, 2001). Finally, research using the rare-word paradigm has found that difficult semantic retrievals recruit inhibitory processes: When subjects struggle to recall the meaning of an unusual, infrequently encountered word that is weakly represented in memory, related concepts appear to be impaired (Barnhardt, Glisky, Polster, & Elam, 1996;Dagenbach, Carr, & Barnhardt, 1990; see also Thompson-Schill, 1997 for an interesting discussion of the role of the left prefrontal cortex in controlling selective retrieval from semantic memory). Taken together, these results argue that retrieval induced forgetting is not limited to episodic retrieval, or to taxonomic categories; rather, it is a general consequence arising whenever inhibitory mechanisms are recruited to guide selection in the face of competition from distracting memories.…”
Section: Generalitymentioning
confidence: 68%
“…Thus, an a priori hypothesis for our experiments would have been to assume negative effects, especially for highdominant exemplars. However, adapting an argument provided by Kahan to account for results of Barnhardt et al (1996), we could speculate that possibly, if low-dЈ participants are shown a lowdominant target, they will make a long partial match between the related prime and the target, slowing responses to the target compared with the unrelated prime condition. If the target is a highdominant exemplar, low-dЈ participants will quickly make a complete match between the related prime and target before responding to the target.…”
Section: Retrospective Retrieval Accounts Of Semantic Primingmentioning
confidence: 96%
“…If a competitor substantially overlaps the target in semantic space, enough of its representation may be in the attentional center so as to create facilitation rather than inhibition. This implication was tested recently by Barnhardt, Glisky, Polster, and Elam (1996), who showed that a very difficult retrieval of the meaning of an uncommon word on a prime trial actually facilitated a subsequent lexical decision for a direct synonym of the prime, even though it slowed lexical decision times to semantically similar nonsynonyms. Barnhardt et al argued that the facilitation of synonyms provides strong support for the centersurround theory because synonyms should occupy a region in semantic space that overlaps with the target, preventing them from being suppressed.…”
Section: Center-surround Theorymentioning
confidence: 99%
“…In particular, the reduction in retrieval-induced forgetting associated with target-competitor similarity in Experiment 1 may be produced by mechanisms similar to those thought to be at work in the study of Barnhardt et al (1996). If we assume that encoding target-competitor similarities brings a target and a competitor closer together in semantic space, some portion of the unpracticed competitor's representation might fall within the attentional center of the item being recalled during retrieval practice.…”
Section: Center-surround Theorymentioning
confidence: 99%